SPARC Negatively Correlates With Prognosis After Transarterial Chemoembolization and Facilitates Proliferation and Metastasis of Hepatocellular Carcinoma via ERK/MMP Signaling Pathways - Liu, Yao; Feng, Ying; Wang, Xiaojing; Yang, Xue; Hu, Ying; Li, Yuxin; Zhang, Qun; Huang, Yunyi; Shi, Ke; Ran, Chongping; Hou, Jie; Jiang, Li; et al. (Frontiers in Oncology, 2020)
Background: Transarterial chemoembolization (TACE) represents a widely accepted treatment procedure for intermediate stage or unresectable hepatocellular carcinoma (HCC). However, few studies have evaluated serologic prognosis factors in patients with HCC before TACE. Secreted protein acidic and rich in cysteine (SPARC) is a matricellular glycoprotein affecting tumorigenesis and metastasis, and leading to poor prognosis in HCC. Therefore, to further explore the potential prognosis value of SPARC, the expression levels in the plasma of patients and its potential molecular mechanisms underlying the regulation of HCC were investigated in this study. Materials and methods: The study population included 43 patients with HCC who underwent TACE. To evaluate the expression of SPARC in different grades of pathological tissues, the immunohistochemistry was performed on tissues from 89 patients with HCC. Lentiviral vectors carrying interference sequences, as well as vectors harboring the complete open reading frame of SPARC for the knockdown or overexpression of SPARC in HuH-7 or HepG2 cells, respectively, allowed us to determine the biological functions of SPARC in vitro and in vivo. We also evaluated the levels of phosphorylated extracellular signal-regulated kinases 1/2 (p-ERK1/2) and matrix metalloproteinases 2/9 (MMP2/9) activation. Results: The association between serum levels of SPARC and the survival at different TNM and Barcelona-Clinic Liver Cancer (BCLC) stages in patients with HCC undergoing TACE were evaluated. We observed a significant upregulation of SPARC in high grade HCC tissues, predicting unfavorable prognosis and suggesting an important tumor-promoting effect of SPARC. Functional studies indicated that downregulation of SPARC contributed to the inhibition of proliferation and metastasis of HuH-7 cells in vitro, whereas its overexpression led to opposite phenotypes. Mechanistically, decreased expression of SPARC resulted in dephosphorylation of ERK1/2 and deactivation of MMP2/9, thereby inhibiting growth and metastasis of HCC. Importantly, low expression levels of SPARC inhibited the formation of subcutaneous tumors in nude mice. Conclusions: SPARC was found to facilitate proliferation and metastasis of HCC via modulation of the ERK1/2-MMP2/9 signaling pathways. Our research has provided a glimpse on the biological mechanism of SPARC and might contribute to the eventual treatment of liver cancer.